Fifty years of female suffrage in colombia 1954: for the conquest of vote. 2004: for the extension of female citizenship (2005)
This article makes a memory reconstruction and a balance of the steps taken by Colombian women in the last decades in regards to the commemoration of 50 years of female suffrage. This paper presents the main reflections and conclusions of the forums organized by a group of regions and Bogota, congresswomen, national institutions, female collective groups and international funds for development which took place in August, 2004. The first forum was dedicated to memory and history; the second to the participation and construction of democracy; and the last one proposed a consolidation agenda of female citizenship viable for the country.